'Whatever happened to the Mexican Green Revolution?'. Issue 9 (20th October 2020) - Harwood, Jonathan
ABSTRACT: References to 'the Green Revolution' in the development literature over the last decade or two are nearly always selective. The revolution is seen as having taken place from the 1960 s in Asia; almost no one refers to the green revolution programs in Latin America during the 1940 s and '50 s. Remarkably, this silence extends even to the Rockefeller Foundation's Mexican Agricultural Program whose importance – not least for the subsequent programs in Asia – was widely recognized by the 1960 s. It is unlikely that the development community is ignorant of the Green Revolution's history. Instead I argue that the Mexican program has been conveniently forgotten because, despite its very substantial impact upon wheat production, it failed utterly to alleviate rural poverty and malnutrition. For those who regard a 'new Green Revolution' as the only viable way to secure future food supplies, therefore, the Mexican episode is an embarrassment which is best left unmentioned.